Does addiction belong in modernity? Discursive strategies of exclusion in Polish public awareness campaigns. (April 2019) - Kowal-Bourgonjon, Eliza; Jacobs, Geert
Highlights: Mass-media PSAs represent the institutional view on addiction as a social problem. Modernity both generates and excludes the subject position of an addict. Polish PSAs construct the rational, self-managing subject as a role model. Exclusion of addiction is modernity's way of maintaining its hegemony. Abstract: This paper presents theoretical and empirical insights into the discursive construction of addiction as a contemporary social problem in public awareness campaigns. Our data set consists of a sample of public awareness campaigns that were published by the Polish National Bureau for Drug Prevention between the year 2000 and 2015. Based upon Laclau and Mouffe's discourse theory, as well as Herschinger's concept of 'strategy', four strategies of exclusion were identified: (1) silencing the addict, (2) constructing an idealised role model, (3) creating binary oppositions and (4) pairing closeness with control. Addiction is shown to be understood as a highly anti-modern phenomenon that prevents addicts from full participation in modern society and serves both as a tool of exclusion and a basis for institutional intervention and surveillance. We argue that these strategies are modernity's way of maintaining hegemony, obscuring its possible role in creating the addict and marginalising alternative discourses.